Reformasi Hukum Tanah dalam Rangka Perlindungan Hak Atas Tanah Perorangan dan Penanam Modal dalam Bidang Agrobisnis - Darwin Ginting (Fakultas Hukum Universitas Islam Indonesia, 2011)
The problem which would be discussed is how the policy format of law in the future mentioned the rights protection on individual land property and investment in agribusiness field. This research is juridical normative research using statutory approach. Data processing and analysis which was performed is descriptive qualitative. The result of the research concluded that; first, it is necessary to form regulation of land property rights, so that it could support the certainty of land property rights for individual and the certainty of law for every sector of capital investment. Second, the formation of the legislation prioritized the citizen’s aspiration and the community of agribusiness industrial field.Key words : Reformation, land titles, private and agribusiness